2009
DOI: 10.1073/pnas.0900617106
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of internal body time by blood metabolomics

Abstract: Detection of internal body time (BT) via a few-time-point assay has been a longstanding challenge in medicine, because BT information can be exploited to maximize potency and minimize toxicity during drug administration and thus will enable highly optimized medication. To address this challenge, we previously developed the concept, ''molecular-timetable method,'' which was originally inspired by Linné 's flower clock. In Linné 's flower clock, one can estimate the time of the day by watching the opening and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
183
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 247 publications
(192 citation statements)
references
References 44 publications
6
183
1
2
Order By: Relevance
“…3A and B-blue shading). Metabolomics indicate that approximately 20% of metabolites fluctuate with a circadian variation [69][70][71]. Blood glucose levels undergo time-of-day variation in humans and rodent models [72].…”
Section: Clocks and Metabolismmentioning
confidence: 99%
“…3A and B-blue shading). Metabolomics indicate that approximately 20% of metabolites fluctuate with a circadian variation [69][70][71]. Blood glucose levels undergo time-of-day variation in humans and rodent models [72].…”
Section: Clocks and Metabolismmentioning
confidence: 99%
“…20 Furthermore, a recent study using blood metabolome analysis revealed that hundreds of metabolites in mouse plasma show robust circadian oscillation. 21 Third, and more interestingly, recent studies demonstrated that transcriptional coactivators play a critical role in the integration of clock and metabolic functions. PPAR-c coactivator-1a (PGC-1a), an important metabolic coactivator, modulates circadian clocks and energy metabolism simultaneously through coactivating RORs.…”
mentioning
confidence: 99%
“…In mammals, for example, several clock genes regulate circadian gene expression in central and peripheral clock tissues (3)(4)(5)(6)(7)(8)(9), as well as metabolites in the blood (10)(11)(12)(13)(14)(15). Reflecting circadian regulation of such processes, the potency and toxicity of administered drugs depends on an individual's body time (BT) (16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…One conventional way to estimate human internal body time is to periodically sample for more than 24 h the level of melatonin or cortisol, which have robust circadian oscillations in the blood (10)(11)(12). Although this strategy directly measures internal body time, it requires labor-intensive constant sampling under controlled environmental conditions to reveal metabolite peaks and rhythms.…”
mentioning
confidence: 99%
See 1 more Smart Citation